Emotion in Action : Thucydides and the Tragic Chorus - Visvardi, Eirene (Mnemosyne, Supplements Ser, 2015)
Contents -- Acknowledgments -- Chapter 1 Choral Emotions and Collective Passions: Questions and Approaches, Old and New -- 1 Introduction -- 2 Preliminaries: Assumptions and Questions -- 3 Aristotle and the (Tragic) Emotions: Uses and Limitations -- 4 Collectively Dancing the Emotions -- 4.1 The Tragic Chorus -- 4.2 Rethinking Choral Action(s) -- 4.3 On Methodology -- 5 Collective Emotion Outside the Theater: Thucydides' History -- 6 Civilizing the Passions? Theorizing Emotion in Action -- Chapter 2 Contextualizing Choral Emotions: Thucydides and Collective Psychology -- 1 Preliminaries: 'Feeling Together' in Thucydides -- 2 Collective Emotion within the City-State -- 2.1 Ideal Emotion in Athenian Democracy: The Citizen-Lover -- 2.2 Unideal Emotions within the State: The Plague -- 2.3 Pericles and the Emotions of the Dêmos: Phobos, Orgê, and Gnômê -- 2.4 The Emotions of Stasis: The Oligarchic Coup in Athens -- 2.5 The Quintessential Emotions of Stasis: Corcyra -- 2.6 Reason, Passion, and Human Nature -- 3 Collective Emotion and Interstate Relations -- 3.1 The Case of Mytilene -- 3.2 The Sicilian Expedition -- 4 Closing Thoughts: Collective Emotion-Potential and Shortcomings -- Chapter 3 Emotion in Aeschylus' Active Choruses -- 1 Defining Active Choruses -- 2 Aeschylus, Eumenides -- 3 Aeschylus, Supplices -- 4 Aeschylus, Seven Against Thebes -- Chapter 4 Enacting Choral Emotion: Sophocles and Euripides -- 1 Defining Enactment -- 2 Sophocles, Philoctetes -- 3 Euripides, Bacchae -- Coda: The Value(s) of Collective Emotion in Action -- Bibliography -- Index of Subjects -- Index of Sources.